An approach to alternative post-deposition treatment in CdTe thin films for solar cell application - Harif M.N.; Rahman K.S.; Rosly H.N.; Chelvanathan P.; Doroody C.; Misran H.; Amin N. (Academic Press, 2023)
Cadmium chloride; Cadmium telluride; Carrier concentration; Copper compounds; Deposition; Energy gap; II-VI semiconductors; Magnesium compounds; Semiconductor doping; Silver compounds; Thin film solar cells; Thin films; X ray diffraction analysis; Characterization tools; Close spaced sublimation; Hall effect measurement; Magnesium chlorides; Optoelectronic properties; Post deposition treatment; Solar-cell applications; Structural parameter; Chlorine compounds